Khrōngkān watthanatham Thai sāiyai chumchon Čhangwat Phrǣ : kānsongsœ̄m khlang samō̜ng læ phūmpanyā thō̜ngthin (Samnakngān Watthanatham Čhangwat Phrǣ, 2009)
Promotion of culture as a cultural project in Phrae Province, Northern Thailand.